2017
DOI: 10.1136/archdischild-2016-311581
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes of extremely low birthweight infants randomised to different PCO 2 targets: the PHELBI follow-up study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
1
32
0
2
Order By: Relevance
“…Capnography during PSG is challenging, 16 particularly in neonates. Although existing literature suggests no effect of permissive hypercapnia, during the first few days of life, on neurodevelopmental outcome, 17,18 there are no published data on the effect of sustained hypercapnia during sleep on neurocognitive outcomes in preterm infants.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Capnography during PSG is challenging, 16 particularly in neonates. Although existing literature suggests no effect of permissive hypercapnia, during the first few days of life, on neurodevelopmental outcome, 17,18 there are no published data on the effect of sustained hypercapnia during sleep on neurocognitive outcomes in preterm infants.…”
Section: Introductionmentioning
confidence: 92%
“…36 Existing literature suggests no effect of permissive hypercapnia on neurodevelopmental outcome. 17,18 Additionally, the Childhood Adenotonsillectomy, or CHAT, trial did not report any correlation of percentage of total sleep time (TST) with ETCO 2 > 50 mm Hg with changes on the cognitive and behavioral assessment at median age of 7.1 years. The median ETCO 2 , while asleep, of that study sample was 45 mm Hg, 34 which is a little lower than in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a considerable overlap in actual PCO 2 values between the study groups. Although the randomized assignment to a target group did not significantly influence important clinical outcomes, there were trends suggesting that the higher target range could be associated with an increased risk of bronchopulmonary dysplasia (BPD) and necrotizing enterocolitis (NEC) [15], but does not affect neurodevelopment [16]. Effects such as these may be more evident in analyses based on actual PCO 2 values rather than on the prescribed target ranges.…”
Section: Introductionmentioning
confidence: 99%
“…The PHELBI study (a large prospective randomized multicenter study examining the adverse effects of permissive hypercapnia done for 2 weeks following very premature births) found permissive hypercapnia did not further compromise neurodevelopmental outcomes at age 2 years. 10 In this study, hypercapnia was identified on overnight PSG performed a mean of 4 months following birth.…”
mentioning
confidence: 99%